Kerion Caused by Microsporum Audouinii in a Child - Fernandes, S (2014)
Kerion celsi is rarely associated with Microsporum audouinii infection. We report the case of a 3-year-old girl with a kerion celsi caused by M. audouinii and successfully treated with oral terbinafine. Fungi identification was made by macro and microscopical colony morphology analyses and molecular (genotypic) studies.